3D ordered carbon/SnO2 hybrid nanostructures for energy storage applications. (20th October 2018) - Hyun, Gayea; Cho, Su-Ho; Park, Junyong; Kim, Kisun; Ahn, Changui; Tiwari, Anand P.; Kim, Il-Doo; Jeon, Seokwoo
Abstract: Increasing the specific capacity and cycle life of graphitic carbon anodes is crucial for realizing high-performance lithium ion batteries. Herein, we introduce a new class of graphitic carbon anodes comprising highly ordered three-dimensional nanostructures decorated with SnO2 nanoparticles. The inch-scale, nanostructured graphitic carbon matrices are prepared by supported pyrolysis of epoxy templates patterned by advanced optical lithography. During the subsequent decoration process, the SnO2 nanoparticles are densely formed on the matrix without agglomeration since the periodic nanostructured matrix provides a homogeneous site for nucleation and growth. The surface coverage of the decorated SnO2 nanoparticles and the mass relative to the graphitic carbon are >80% and ∼50 wt%, respectively. The resulting nanostructured C/SnO2 composite monoliths can be assembled solely into LIB coin cells without the aid of binders and conducting agents. The achieved specific capacity and retention are 692 mAh g −1 and 87.31% (at 70th cycle), respectively, which is superior to those of nanostructured carbon anodes prepared in a similar way.